AN ANALYSIS OF CHILD PORNOGRAPHY AND VIRTUAL SEXUAL SOLICITATION - Kumar, Sanjeev; Pallathadka, Harikumar; Kirana Pallathadka, Laxmi (International Journal of Psychosocial Rehabilitation, 2021)
Child pornography on the internet is becoming an increasingly apparent issue in today’s society. Child pornographers have discovered a convenient forum for distributing terrible images of children who have been sexually assaulted due to increased home Computer use and more easily accessible access to the World Wide Web during the last decade. Additionally, police and attorneys worldwide have discovered that identifying and Prosecution of cyberchild pornographers has become time-consuming, with a high failure rate of putting offenders in prison. When fighting online child pornography, law enforcement authorities’ techniques presently in use may be deemed archaic and ineffective. This article examines the main social, legal, and technical problems that people, legislators, and law enforcement officials are confronted with regarding cyber child pornography. Thus, this paper examines how children are exposed to violence through their use of the internet, as well as the need for parents, schools, government, and all stakeholders to take protective and preventive measures to ensure children’s safety in cyberspace, including through comprehensive education and child protection standards.